Clean Donor Oxidation Enhances the H2 Evolution Activity of a Carbon Quantum Dot–Molecular Catalyst Photosystem. (29th June 2016) - Martindale, Benjamin C. M.; Joliat, Evelyne; Bachmann, Cyril; Alberto, Roger; Reisner, Erwin
Abstract: Carbon quantum dots (CQDs) are new‐generation light absorbers for photocatalytic H2 evolution in aqueous solution, but the performance of CQD‐molecular catalyst systems is currently limited by the decomposition of the molecular component. Clean oxidation of the electron donor by donor recycling prevents the formation of destructive radical species and non‐innocent oxidation products. This approach allowed a CQD‐molecular nickel bis(diphosphine) photocatalyst system to reach a benchmark lifetime of more than 5 days and a record turnover number of 1094±61 molH2 (molNi ) −1 for a defined synthetic molecular nickel catalyst in purely aqueous solution under AM1.5G solar irradiation.